Role of Epinephrine-mediated β-Adrenergic Mechanisms in Hypoglycemic Glucose Counterregulation and Posthypoglycemic Hyperglycemia in Insulin-dependent Diabetes Mellitus - Popp, Dennis A. (1982)
Initially euglycemic (overnight insulin-infused) patients with insulin-dependent diabetes mellitus (IDDM), compared with nondiabetic controls, exhibit similar, but somewhat delayed plasma glucose nadirs, delayed glucose recovery from hypoglycemia, and posthypoglycemic hyperglycemia after the rapid intravenous injection of 0.075 U/kg of regular insulin. These abnormalities are associated with and potentially attributable to markedly diminished glucagon secretory responses, partially reduced epinephrine secretory responses and delayed clearance of injected insulin in the diabetic patients. Because glucagon normally plays a primary role in hypoglycemic glucose counterregulation and enhanced epinephrine secretion largely compensates for glucagon deficiency, we hypothesized that patients with IDDM, who exhibit diminished glucagon secretory responses to hypoglycemia, would be more dependent upon epinephrine to promote glucose recovery from hypoglycemia than are nondiabetic persons. To test this hypothesis, glucose counterregulation during β-adrenergic blockade with propranolol was compared with that during saline infusion in both nondiabetic controls and in patients with IDDM. Glucose counterregulation was unaffected by β-adrenergic blockade in controls. In contrast, glucose recovery from hypoglycemia was significantly impaired during β-adrenergic blockade in diabetic patients. This finding confirms the hypothesis that such patients are more dependent upon epinephrine-mediated β-adrenergic mechanisms to promote glucose recovery from hypoglycemia and indicates that the measured deficiency of glucagon secretion is functionally important in patients with IDDM. Further, in the time frame of these studies, posthypoglycemic hyperglycemia was prevented by β-adrenergic blockade in these patients. There was considerable heterogeneity among the diabetic patients with respect to the degree to which β-adrenergic blockade limited the posthypoglycemic rise in plasma glucose. This rise was directly related to the degree of residual glucagon secretion and inversely related to plasma-free insulin concentrations. Thus, we conclude: (a) that patients with IDDM are, to varying degrees, dependent upon epinephrine-mediated β-adrenergic mechanisms to promote glucose recovery from hypoglycemia and that the degree of this dependence upon epinephrine is an inverse function of the residual capacity to secrete glucagon in response to hypoglycemia in individual patients; (b) that sympathoadrenal activation, coupled with the inability to secrete insulin, plays an important role in the pathogenesis of posthypoglycemic hyperglycemia in patients with IDDM.